The Role of Short Stories in Improving Vocabulary of Kurdish EFL Learners - Ismael, Darya Abdalrahman (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
The current study aimed to investigate the effects of short stories on vocabulary development of pre-intermediate Kurdish EFL leaners. To this end, 40 students enrolled in Raparin Non- Governmental Institute for Computer Science in Kurdistan region of Iraq, participated in this study. To determine the level of the participants, Oxford Placement Test was administered and the participants were randomly placed in two equal groups (control & experimental). A vocabulary proficiency test (pre-test) was also administered to the participants to see whether they were homogenous in terms of their vocabulary knowledge. During the study, the experimental group used the course book (Hughes, 2006) and short stories (Lost and Found, Anniversary Day, Act like the Others, A Secret Talent, and Online Dating and True Adventure Stories) as taching materials while the control group used only the course book. To see the difference between the control and experimental groups at the end of the course, the same vocabulary proficiency test was given to the participants in both groups as a posttest. The participants also completed the vocabulary learning strategy survey. Data collected through the aforementioned instruments were analyzed using independent samples a t-test to compare the mean scores of the control and experimental groups. Results indicated that the experimental group who were exposed to short stories out performed the control group in the posttest. Survey feedback analysis showed that students in both group used determination strategy more than the other four strategies.

ÖZ: Bu çalışmanın amacı alt orda seviye Kürt öğrencilerin İngilizce kelime bilgisi geliştirmeleri için kısa hikâyelerin etkilerini araştırmaktır. Bu amaçla Irak Kürdistan bölgesinden Raparin Bilgisayar Bilimleri kurumundan 40 öğrenci seçilmiştir. Kişilerin İngilizce seviyelerinin belirlenmesi için Oxford Placement Test uygulanmış ve kişiler gelişigüzel olarak 2 farklı guruba ayrılmıştır (kontrol ve deney grupları). Kişilerin kelime bilgisi anlamında türdeş olup olmadıklarını da bir ön sınavla kontrol edilmiştir. Çalışmada deney gurubu materyal olarak ders kitabı (Hughes, 2006) ve kısa hikayeler kullanırken(Lost and Found, Anniversary Day, Act like the Others, A secret Talent, and Online Dating and True Adventure Stories), kontrol grubu sadece ders kitabını kullandı. Farklılık oluşup oluşmayacağının gözlenmesi amaçlı 2 gruba kurs sonunda aynı kelime bilgisi sınavı uygulandı. Katılımcılar ayrıca kelime öğrenme stratejileri anketi de tamamladılar. İki gurubun sınav sonuçları ortalaması analiz edildi. Sonuçlar kısa hikâyelere maruz kalan deney gurubundaki kişilerin kontrol gurubuna göre daha başarılı olduklarını göstermektedir. Anket sonuçlarına göre ise 2 grup da kararlılık stratejisini diğer 4 stratejiden daha fazla kullandı.
Master of Arts in English Language Teaching (ELT). Thesis (M.A.)--Eastern Mediterranean University, Faculty of Education, Dept. of English Language Teaching, 2017. Supervisor: Assoc. Prof. Dr. Javanshir Shibliyev.
Keywords: English Language--Study and Teaching; English language--Textbooks for foreign speakers--Short stories; Vocabulary learning strategies; Short Story; Pre-intermediate; Kurdish EFL students; English Language Teaching